Beta half logistic distribution – A new probability model for lifetime data. Issue 4 (3rd July 2016) - Jose, Joby K.; Manoharan, M.
Abstract: Introducing a new flexible model for lifetimes called Beta half Logistic distribution by compounding the Beta distribution and half logistic distributions, we explore its analytical characteristics and statistical properties. The maximum likelihood estimates of the model parameters are discussed and the usefulness of the new model is illustrated by means of data on remission times of bladder cancer patients.